Personal finance blogs: Helpful tool for consumers with low financial literacy or preaching to the choir?. (20th December 2017) - Hoffmann, Arvid; Otteby, Katarina
Abstract: Recent transitions from defined benefit to defined contribution plans assign greater individual responsibility to consumers to prepare for retirement and make consequential financial choices. However, many consumers are ill‐equipped to do so, considering overall low levels of financial literacy. At the same time, there is increasing controversy about the effectiveness of traditional financial education, such as high school financial education, counselling and seminars or workshops. Alternative sources of (just‐in‐time) financial training or advice may be needed to financially empower consumers and help them make important financial decisions. In the light of these developments, this study investigates if consumers perceive personal finance blogs as a helpful alternative in acquiring financial knowledge, and which factors influence perceived helpfulness of and intention to use personal finance blogs. Using Structural Equation Modelling to analyse data from a sample of U.S. consumers, the results of this study uncover that financial literacy and susceptibility to informational influence have a significant positive association with perceived helpfulness. Perceived financial uncertainty, which refers to uncertainty in terms of consumers' perceived ability to accurately predict their future financial needs, has a significant negative association with perceived helpfulness of and intention to use personal finance blogs. Finally, perceived helpfulness of a personal finance blog is a significant positive predictor of consumers' intention to use it. Overall, the findings suggest that personal finance blogs are preaching to the choir, since the consumers who are most likely to use personal finance blogs seem to need them the least given their higher levels of financial literacy and lower levels of perceived financial uncertainty. Taken together, the findings shed light on the potential users of personal finance blogs and underline the challenges of a 'one‐size‐fits‐all' financial education. This study aids in assessing personal finance blogs as an online resource which is scarcely researched, but which has the potential to provide just‐in‐time financial education to consumers across the world.